Mortization, Research and Development Expense, Unusual/Exceptional Item Relevance for Street Earnings - Zulfikar Ikhsan Pane (Journal of Social Science, 2021)
This study is motivated by the phenomenon of investors' concern when they saw earnings from companies prepared by accounting managers who have self-interest tendencies. As a result, investors may be misled in companies' assessments. Based on this phenomenon, this study helps investors to get the relevant value of earnings by eliminating three items in the income statement so it becomes a value known as street earnings. Street earnings are values that are generally generated by securities analysts. This value is the result of recalculation of accounting earnings excluding non-recurring items, wherein in this study, the items are amortization, research and development expenses, and unusual/exceptional items. This research focuses on the relevance of these three values especially unusual/exceptional items as a novelty. This relevance is calculated by looking at the strength of relations between three variables partially to year-end stock prices based on the value of R square. Secondary data used from manufacturing companies in Indonesia was obtained by the OSIRIS database from the 2015 - 2020 period. As a result, none of the three variables has strong relations with stock prices, which means three variables are irrelevant and should exclude in the calculation of street earnings to make street earnings relevant. The limitation of this study is research and development expense does not refer to companies specific activities, so irrelevant results does not mean research activities are useless. From these limitations, further research is comparisons of the relevance between the disclosure of research and development activities and research and development expense